2018
DOI: 10.1158/0008-5472.can-17-1394
|View full text |Cite
|
Sign up to set email alerts
|

Cancer-Associated MORC2-Mutant M276I Regulates an hnRNPM-Mediated CD44 Splicing Switch to Promote Invasion and Metastasis in Triple-Negative Breast Cancer

Abstract: Triple-negative breast cancer (TNBC) is the most lethal subtype of breast cancer, with a high propensity for distant metastasis and limited treatment options, yet its molecular underpinnings remain largely unknown. Microrchidia family CW-type zinc finger 2 (MORC2) is a newly identified chromatin remodeling protein whose mutations have been causally implicated in several neurologic disorders. Here, we report that a cancer-associated substitution of methionine to isoleucine at residue 276 (M276I) of MORC2 confer… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
88
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 83 publications
(96 citation statements)
references
References 49 publications
3
88
0
Order By: Relevance
“…It is reported that MORC2 promoted breast cancer invasion and metastasis through a PRD domain‐mediated interaction with catenin delta 1 . Recently, it has been shown that MORC2‐mutant M276I promotes metastasis of triple‐negative breast cancer by regulating CD44 splicing . Moreover, MORC2 promotes cancer stemness and tumorigenesis by facilitating DNA methylation‐dependent silencing of Hippo signaling in hepatocellular carcinoma .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is reported that MORC2 promoted breast cancer invasion and metastasis through a PRD domain‐mediated interaction with catenin delta 1 . Recently, it has been shown that MORC2‐mutant M276I promotes metastasis of triple‐negative breast cancer by regulating CD44 splicing . Moreover, MORC2 promotes cancer stemness and tumorigenesis by facilitating DNA methylation‐dependent silencing of Hippo signaling in hepatocellular carcinoma .…”
Section: Introductionmentioning
confidence: 99%
“…12 Recently, it has been shown that MORC2-mutant M276I promotes metastasis of triple-negative breast cancer by regulating CD44 splicing. 13 Moreover, MORC2 promotes cancer stemness and tumorigenesis by facilitating DNA methylation-dependent silencing of Hippo signaling in hepatocellular carcinoma. 14 Additionally, MORC2 was found to be one of the mutation hotspot oncogenes in CRCs with microsatellite instability.…”
mentioning
confidence: 99%
“…Secondary Abs for immunoblotting and immunofluorescence were from Cell Signaling Technology. Immunoblotting, IP, and immunofluorescence have previously been described . Briefly, for immunoblotting analyses, cells were lysed in modified RIPA buffer (50 mmol/L Tris‐HCl, pH 7.4, 150 mmol/L NaCl, 1% NP‐40, 0.25% sodium deoxycholate, 0.1% SDS, and 1 mmol/L EDTA) containing 1× protease inhibitor cocktail and 1× phosphatase inhibitor cocktail (Bimake, Shanghai, China).…”
Section: Methodsmentioning
confidence: 99%
“…Immunoblotting, IP, and immunofluorescence have previously been described. 27,30 Briefly, for immunoblotting analyses, cells were lysed in modified RIPA buffer (50 mmol/L Tris-HCl, pH 7.4, 150 mmol/L NaCl, 1% NP-40, 0.25% sodium deoxycholate, 0.1% SDS, and 1 mmol/L EDTA) containing 1× protease inhibitor cocktail and 1× phosphatase inhibitor cocktail (Bimake, Shanghai, China). Proteins were quantified using the bicinchoninic acid assay (Yeasen, Shanghai, China), resolved by SDS-PAGE, and transferred onto PVDF membrane (Millipore, Billerica, MA, USA).…”
Section: Antibodies Immunoblotting Immunoprecipitation and Immunmentioning
confidence: 99%
“…Immunoblotting analysis, immunoprecipitation assays, and immunofluorescent staining were performed as described previously in details. [39][40][41]…”
Section: Antibodies Immunoblotting Immunoprecipitation Assays Anmentioning
confidence: 99%